Mozilge New toeic : - Byeongjae, Park (Tổng hợp Thành phố Hồ Chí Minh, 2009)
In this part, you will read a selection of texts, such as magazine and newspaper articles, letters, and advertisements. Each text is followed by several questions. Select the best answer for each question and mark the letter (A), (B), (C), or (D) on your answer sheet.